Implantable Osmotic Transport Device Can Reduce Edema After Severe Contusion Spinal Cord Injury - Hale, Christopher; Yonan, Jennifer; Batarseh, Ramsey; Chaar, Roman; Jonak, Carrie R.; Ge, Shaokui; Binder, Devin; Rodgers, Victor G. J. (Frontiers in Bioengineering and Biotechnology, 2020)
Recent findings from the ISCoPe study indicate that, after severe contusion to the spinal cord, edema originating in the spinal cord accumulates and compresses the tissue against the surrounding dura mater, despite decompressive laminectomy. It is hypothesized that this compression results in restricted flow of cerebrospinal fluid (CSF) in the subarachnoid space and central canal and ultimately collapses local vasculature, exacerbating ischemia and secondary injury. Here we developed a surgically mounted osmotic transport device (OTD) that rests on the dura and can osmotically remove excess fluid at the injury site. Tests were performed in 4-hour studies immediately following severe (250 kD) contusion at T8 in rats using the OTD. A 3-hour treatment with the OTD after 1-hour post injury significantly reduced spinal cord edema compared to injured controls. Our simple mathematical interpretation implies that this modest reduction in edema may be significant enough to relieve compression of local vasculature and restore flow of CSF in the region. In addition, we determined the progression of edema up to 28 days after insult in the rat for the same injury model. Results showed peak edema at 72 hours. These preliminary results suggests that incorporating the OTD to operate continuously at the site of injury throughout the critical period of edema progression, the device may significantly improve recovery following contusion spinal cord injury.